Portable High Voltage Integrated Harvesting-Storage Device Employing Dye-Sensitized Solar Module and All-Solid-State Electrochemical Double Layer Capacitor - Scalia, Alberto; Varzi, Alberto; Lamberti, Andrea; Jacob, Timo; Passerini, Stefano (Frontiers in Chemistry, 2018)
A dye-sensitized solar module (DSSM) and a high voltage all-solid-state electrochemical double layer capacitor (EDLC) are, for the first time, implemented in a compact Harvesting-Storage (HS) device. Conductive glass is employed as current collecting substrate for both DSSM and EDLC, leading to a robust and portable final structure. The photovoltaic section is constituted by a 4 series cells W-type module, while in the storage section an EDLC employing an ionic liquid-based polymeric electrolyte (a mixture of polyethylene oxide and N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, PEO-Pyr14TFSI) and activated carbon electrodes is used. The solid state EDLC is first characterized individually to determine its electrochemical performance before successfully proving the integration with the DSSM. The harvesting-storage properties of the integrated photo-capacitor are evaluated through photo-charge and subsequent discharge protocols performed at two different discharge currents, showing that in this configuration the EDLC unit can be effectively charged up to 2.45 V.